In struggle against Jim Crow : Lulu B. White and the NAACP, 1900-1957 - Pitre, Merline, 1943- (Centennial series of the Association of Former Students, Texas A & M University, 1999)
African American women have played significant roles in the ongoing struggle for freedom and equality, but relatively little is known about many of these leaders and activists. Most accounts of the civil rights movement focus on male leaders and the organizations they led, leaving a dearth of information about the countless black women who were the backbone of the struggle in local communities across the country. At the local level women helped mold and shape the direction the movement would take. Lulu B. White was one of those women in the civil rights movement in Texas. Executive secretary of the Houston branch of the NAACP and state director of branches, White was a significant force in the struggle against Jim Crow during the 1940s and 1950s. She was at the helm of the Houston chapter when the Supreme Court struck down the white primary in Smith v. Allbright, and she led the fight to get more blacks elected to public office, to gain economic parity for African Americans, and to integrate the University of Texas. Author Merline Pitre places White in her proper perspective in Texas, Southern, African American, women's, and general American history; points to White's successes and achievements, as well as the problems and conflicts she faced in efforts to eradicate segregation; and looks at the strategies and techniques White used in her leadership roles. Pitre effectively places White within the context of twentieth-century Houston and the civil rights movement that was gripping the state. In Struggle Against Jim Crow is pertinent to the understanding of race, gender, interest group politics, and social reform during this turbulent era.--From jacket flap.